An Intelligent Agent for Automated Test Generation from OpenAPI Specifications - Vilela, Ricardo F.; Andrade, Stevão Alves de; Santos, Eduardo B. F.; Silva, Williamson; Valle, Pedro H. D. (Anais do Workshop sobre Bots na Engenharia de Software (WBOTS); 2025: Anais do II Workshop sobre Bots na Engenharia de Software, 2025)
Context: The widespread adoption of RESTful APIs demands effective contract validation, especially in critical domains. Motivation: Tools such as Postman and Newman automate test execution, but test creation remains manual, error-prone, and difficult to maintain. Objective: This work proposes an intelligent agent based on LLMs to interpret OpenAPI documents and automatically generate test collections. Method: The solution fragments OpenAPI documents by endpoint, generates specialized prompts, and uses an LLM via OpenRouter to create automated tests, validated with Newman on a public (anonymized) API. Results: Execution produced 34 requests, of which 12 were successful, 14 had critical failures (malformed URIs), and 8 contained structural or semantic errors. The results demonstrate feasibility and reduced manual effort, while indicating the need for further validation and refinement for CI/CD use.